Disaster management of emergency workers: psychological perspective - Mohd Dahlan A. Malek; Ida Shafinaz Mohd Kamil; Muhammad Idris Bahari (Fakulti Psikologi dan Pendidikan, 2021)
This paper discusses the concept of disaster, the level of disaster and how effective disaster management can be implemented by emphasizing the psychological aspects of emergency workers. This paper will also discuss the nature of disasters which is one of the most frequently encountered cases of individuals, communities and countries where it is a universal phenomenon apart from discussing the role of the National Disaster Management Agency (APBN), the Department of Social Welfare (JKM) in dealing with disasters . Natural disasters are events or events that are caused by factors of natural destruction that can cause great damage, loss of property and loss of life. Apart from the victims, emergency workers such as firefighters are sure to have psychological effects as they carry out their duties. Therefore, a quantitative study was conducted to look at the relationship between stress and psychological well-being among firefighters. In addition, how far they are prepared for the psychological aspects of the disaster and rescue work of the victims and how well the psychological well-being and stress of the emergency workers are involved in the emergency situation. The study was conducted in several areas represented by the eastern zone in Kelantan, the northern zone in Kedah and the southern zone in Johor. The research tools used are The American Institute of Stress (AIS) and the Scales of Psychological Well-Being. A total of 604 firefighters were involved in this study. The findings show that there is a link between stress at work and psychological well-being among firefighters in Malaysia and that there should be a psychosocial management module for disaster focused on the psychological aspects of disaster management.